The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s40430-020-2261-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of machining parameters for kerf angle and roundness error in abrasive water jet drilling of CFRP composites with different fiber orientation angles

Abstract: In this study, carbon fiber-reinforced polymer (CFRP) composites with three different fiber orientation angles (M1: [0°/90°] s , M2: [+ 45°/− 45°] s , and M3: [0°/45°/90°/− 45°] s) were drilled (with and without pilot holes) on an abrasive water jet (AWJ) machine and the effect of the drilling parameters on the kerf angle (K) and roundness error (Re) of selected holes was investigated to determine quality characteristics. The first aim of the study was the single-objective optimization of drilling parameters f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 47 publications
2
47
0
4
Order By: Relevance
“…According to this method, in order to perform statistical analysis, the Ra values were converted into the S/N ratio based on the "smaller is the better" approach ( Table 6). While the signal value represents the actual value given by the system that needs to be measured, the noise factor represents the rate of unwanted factors in the measured value [20]. In the experimental study, the Ra value was measured as 0.543 µm, and the average S/N ratio for the Ra value was obtained as 5.503 dB.…”
Section: Experimental Results and Taguchi Optimization For Ra And Vbmentioning
confidence: 99%
See 3 more Smart Citations
“…According to this method, in order to perform statistical analysis, the Ra values were converted into the S/N ratio based on the "smaller is the better" approach ( Table 6). While the signal value represents the actual value given by the system that needs to be measured, the noise factor represents the rate of unwanted factors in the measured value [20]. In the experimental study, the Ra value was measured as 0.543 µm, and the average S/N ratio for the Ra value was obtained as 5.503 dB.…”
Section: Experimental Results and Taguchi Optimization For Ra And Vbmentioning
confidence: 99%
“…Since the softening occurring in the workpiece at high V c (50, m/min) is more than the thermal softening in the cutting tool, a decrease was observed in the Vb value of the cutting tool [3,27]. As seen in the graph in Figure 6b, the increase in the V c and f z at three different V c (20,35 and 50 m/min) and f z (0.03, 0.07 and 0.14 mm/tooth) depends on the increase in the cutting temperature between the cutting tool and the workpiece. It is thought that the chemical reaction occurring between the carbide cutting tool and the workpiece with the influence of increasing temperature affects the wear on the cutting tool and increases Vb formation [3,26,27].…”
Section: Effects Of Cutting Parameters On Flank Wearmentioning
confidence: 93%
See 2 more Smart Citations
“…Under such circumstances, the effective utilization of experimental, modeling, and optimization methodology makes possible a greater improvement in decision-making with new technological solution that can simultaneously satisfy and control the several distinctive as well as contradictory objectives (multi-objective) in order to make the HAJM process as an excellent choice for machining of advanced engineering ceramic and quartz materials. Several statistical and computational approaches such as MRA [1][2][3], RSM [4][5][6][7][8][9], ANN [10][11][12][13] have been applied for predictive modeling and Taguchi method [14][15][16][17][18], GRA [19][20][21][22][23][24][25], desirability function approach of RSM [26][27][28][29][30][31][32], PCA [33,34], TOPSIS [35], GA [11,12,36,37], PSO [38,39] have been employed for parametric as well as process optimization in abrasive jet machining with the help of carrier gas or liquid medium. Extensive studies have been reported by employing various experimental designs, modeling techniques, and optimization approaches in order to assess or investigate th...…”
Section: Introductionmentioning
confidence: 99%